2023
DOI: 10.3390/ijms241814218
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NF-κB in Intracranial Aneurysm Pathogenesis: A Systematic Review

Dilaware Khan,
Jan Frederick Cornelius,
Sajjad Muhammad

Abstract: Intracranial aneurysms (IAs) are abnormal dilations of the cerebral vessels, which pose a persistent threat of cerebral hemorrhage. Inflammation is known to contribute to IA development. The nuclear factor “kappa-light-chain-enhancer” of activated B-cells (NF-κB) is the major driver of inflammation. It increases the expression of inflammatory markers and matrix metalloproteinases (MMPs), which contribute heavily to the pathogenesis of IAs. NF-κB activation has been linked to IA rupture and resulting subarachno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In addition to tissue re-modulation, MMPs contribute to inflammation through their proteinase activity on inflammatory molecules [11]. The lack of these SASP factors or their inhibition by blocking their receptors has been shown to protect against vascular diseases such as atherosclerosis and cerebral aneurysms (CAs) formation and rupture in experimental animal studies [12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%
“…In addition to tissue re-modulation, MMPs contribute to inflammation through their proteinase activity on inflammatory molecules [11]. The lack of these SASP factors or their inhibition by blocking their receptors has been shown to protect against vascular diseases such as atherosclerosis and cerebral aneurysms (CAs) formation and rupture in experimental animal studies [12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%
“… 48 , 49 All of these factors increase cellular and molecular inflammation and are known to induce the formation, progression, and rupture of the IAs. 5 , 36 , 55 , 56 , 57 , 58 , 59 Furthermore, angiotensin II stimulates the release of aldosterone via acting on the adrenal cortex. It should be noted that aldosterone itself mediates inflammation and induces oxidative stress in vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple groups have used this model in various strains of mice and other species with or without modifications. 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 This model has been extensively used to study mechanisms for the development of IA rupture. In addition, many independent groups have used this model to test various pharmacological agents to prevent IA rupture.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in clinical and experimental animal studies, increased activation of NF-κB, MAPKs, and mTOR has been observed in IA and atherosclerotic tissue [20,21,23,33]. NF-κB subunit P50 deficiency in mice, NF-κB decoy in rats, and the blocking of nuclear import of NF-κB in mice has been found to impair IA formation and reduce atherosclerotic lesion size [20,21,23]. Additionally, blocking the nuclear import of NF-κB was found to increase anti-inflammatory M2 macrophages in atherosclerotic lesions [21].…”
Section: Discussionmentioning
confidence: 99%
“…Blocking NF-κB, MAPKs, and mTOR could inhibit cellular senescence and SASP and increase life span [15][16][17][18][19]. Moreover, activation of these pathways has been implicated in cardiovascular diseases, including atherosclerosis and IAs [15,[20][21][22][23]. Animal experimental studies have shown that blocking the activation of these pathways could reduce the formation and progression of atherosclerosis and IAs [15,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%